ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL “PERTEMUAN DUA HATI” KARYA NH. DINI - Nurfitriany '; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Character education became a main issue in education in Indonesia. Social phenomena that we can see now a days is the low values of the characters in self-learners. Examples of problems that we often encounter in our environment is many students violates the religion norm, naughtiness teenage, absence school. This study aims to describe the values of character education in “pertemuan dua hati” by Nh. Dini’s novel which used qualitative descriptive method. Data collection techniques used in this research method is a technique of reading, technical notes, technical literature. In this study, there are three ways to analyze the data: (1) data reduction, (2) Model display, (3) verification conclusion. The study of the novel